Evaluating the Protective Effect of a Combination of Curcumin and Selenium-L-Methionine on Radiation Induced Dual Oxidase Upregulation - Peyman Amini; Saeed Rezapoor; Dheyauldeen Shabeeb; Ahmed Eleojo Musa; Masoud Najafi; Elahe Motevaseli (Tabriz University of Medical Sciences, 2018)
Background: Epidemiological studies have shown an increased incidence of heart diseases among survivors of Chernobyl disaster as well as Hiroshima and Nagasaki atomic bomb explosion. Similar results were observed for lung and left breast cancer patients. Experimental studies have proposed the chronic upregulation of some pro-inflammatory and pro-fibrotic cytokines. Recent studies have shown that upregulation of pro-oxidant enzymes play a key role in the development of late effects of ionizing radiation such as fibrosis. Interleukin-4 (IL-4) and Interleukin-13 (IL-13) are two important cytokines that have shown ability to induce production of free radicals through dual oxidases (Duox) i.e. Duox1 and Duox2. In this study, we aimed to detect the expression of IL-4 receptor-a1 (IL-4Ra1), IL-13 receptor-a2 (IL-13Ra2), Duox1 and Duox2 genes following irradiation of rat's heart. In addition, we evaluated the possible role of the combination of curcumin and selenium-L-methionine on the regulation of these genes. Methods: Twenty rats were divided into 4 groups as follows; G1: control; G2: treatment with the combination of curcumin and selenium-L-methionine; G3: radiation; G4: radiation plus treatment with the combination of curcumin and selenium-L-methionine. Rats were sacrificed 10 weeks after irradiation for detecting the expression of IL-4Ra1, IL-13Ra2, Duox1 and Duox2. Results: Results showed that exposure to ionizing radiation caused upregulation of IL-4Ra1 by more than 4-fold as well as Duox1 and Duox2 by more than 5-fold. However, results showed no detectable expression for IL-13Ra2. Treatment with the combination of curcumin and selenium-L-methionine could attenuate the upregulation of all genes. Conclusion: This study has shown that exposing rat's heart tissues to radiation leads to chronic upregulation of IL-4Ra1, Duox1 and Duox2 as well as pro-oxidant enzymes. Treatment with the combination of curcumin and selenium-L-methionine showed ability to attenuate the upregulation of these genes.